2015
DOI: 10.1021/ol503286s
|View full text |Cite
|
Sign up to set email alerts
|

Chiral and Achiral Basket-Handle Porphyrins: Short Synthesis and Stereostructures of These Versatile Building Blocks

Abstract: Both, chiral and achiral basket-handle porphyrins were synthesized via a short, reliable, and efficient route in multigram quantities. Standard synthetic protocols such as metalation of the macrocycle, halogenation, and borylation of the porphyrin core or alkyl- and arylation with lithium organyls were successfully adapted. The planar-chiral representatives were resolved into their enantiomers, whose absolute configurations were determined by comparison of experimental CD spectra with TDCAM-B3LYP calculated on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…[5] Just recently we showed that short-chain basket handle porphyrins like 3 can be designed to exhibit planar chirality. [6] Two porphyrins linked to each other may also generate a chiral system, as multiple examples by the groups of Osuka, [7] Borovkov, Kobayashi, and Inoue, [8] Chmielewski, [9] Zheng, [10] and our group [11] have shown. We demonstrated the stereodynamic properties of the bisporphyrins 4M (M = Cu, Zn, Pd).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…[5] Just recently we showed that short-chain basket handle porphyrins like 3 can be designed to exhibit planar chirality. [6] Two porphyrins linked to each other may also generate a chiral system, as multiple examples by the groups of Osuka, [7] Borovkov, Kobayashi, and Inoue, [8] Chmielewski, [9] Zheng, [10] and our group [11] have shown. We demonstrated the stereodynamic properties of the bisporphyrins 4M (M = Cu, Zn, Pd).…”
Section: Introductionmentioning
confidence: 96%
“…Selected atropisomers form a chiral axis with the macrocycle. [6] Two porphyrins linked to each other may also generate a chiral system, as multiple examples by the groups of Osuka, [7] Borovkov, Kobayashi, and Inoue, [8] Chmielewski, [9] Zheng, [10] and our group [11] have shown. [5] Just recently we showed that short-chain basket handle porphyrins like 3 can be designed to exhibit planar chirality.…”
Section: Introductionmentioning
confidence: 99%
“… 57 Initially, a relatively short strap was employed (compounds 3a , C 7 H 14 chain), and the porphyrin condensation was performed using standard concentrations of starting materials 3a (3.5 mM) and 4 (7.0 mM), but the target strapped porphyrin 5a was obtained in only 1% yield. Based on reports that increasing the length or rigidity of the strap can lead to higher yields of porphyrin, 26 , 33 we then investigated straps with longer hydrocarbon chains (compounds 3b , C 8 H 16 chain; and 3c , C 10 H 20 chain, or incorporating a para -phenylene unit (compounds 3d and 3e ). Increasing the strap length proved to be advantageous: the porphyrin yield increased from 1 to 8% on extending the hydrocarbon chain from 7 to 10 carbon atoms ( Table 1 , yield at 3.5 mM).…”
Section: Resultsmentioning
confidence: 99%
“…All these eight functionals have been successfully applied for TD-DFT simulations 44,45,73,[84][85][86][87][88] including simulations of the CD spectra of metal complexes. [89][90][91][92][93][94][95][96][97][98][99] In addition to the functionals, two basis sets of different sizes: cc-pVDZ [100][101][102] and cc-pVTZ 42,91,[100][101][102] were considered. As reported previously, for UV and CD spectra simulations the double-zeta basis set is considered to be accurate.…”
Section: ° Computational Detailsmentioning
confidence: 99%